A Study on Customers’ Expectations towards Purchase of Smartphones in India: with Reference to Andhra Pradesh, India - Dokku, Srinivasa Rao; C., Rajesh; Lakshmi, P. Adi (goodwood publishing, 2022)
Purpose: The purpose of this study is to determine Indian consumers' expectations regarding the purchase of cell phones. The survey addresses issues such as what characteristics customers look for in a smartphone before purchasing a mobile phone, what the anticipated price of a smartphone is, etc. Research Methodology: Data were obtained from 250 respondents in Andhra Pradesh, India, using Google Forms. Excel and SPSS software were used to analyze the data. Percentages and the chi-square test were utilized for data analysis. Results: The use of smartphones has substantially increased recently. In the two years following their purchase, the majority of respondents in the selected location upgraded their smartphones. When buying new cell phones, clients prioritize brand, pricing, camera, internal storage, and battery. Custodians prioritize using the Internet to find information such as reviews, prices, models, and the availability of new models. According to a report, consumers anticipate paying less than Rs. 10,000 and expect a smartphone with 4GB of RAM, a 48 MP camera, 68GB of internal memory, and a battery that can hold more than 5000 mAh. Conclusions: This study concludes that consumers prefer affordable smartphones with strong features and rely on online information. Companies should align product features and pricing with these expectations to remain competitive. Limitations: This study only used responses from 250 respondents obtained using Google Forms. Contributions: This study will assist companies that manufacture mobile devices in developing their pricing and other sales strategies and in understanding customer perceptions of purchasing new mobile devices.